2015
DOI: 10.1016/j.jvs.2015.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular repair of Stanford B aortic dissection using two stent grafts with different sizes

Abstract: Short-term outcomes showed TSI to be a flexible and effective approach to accurately repair Stanford B aortic dissection that could potentially address the limitations of currently available stent grafts. Further prospective clinical studies are warranted to evaluate its long-term efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 20 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…Huang et al 19 suggested the strategy of using two stent grafts with different sizes. In their series, they used tapered stent grafts in a 10-mm-diameter span from the cranial portion to the caudal portion of the stent.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al 19 suggested the strategy of using two stent grafts with different sizes. In their series, they used tapered stent grafts in a 10-mm-diameter span from the cranial portion to the caudal portion of the stent.…”
Section: Discussionmentioning
confidence: 99%
“…One traditional approach is to cover the descending aorta with extended stent graft. 21 Importantly, according to the findings in this study, a novel approach of pre-emptive thoracic false lumen embolization combined with stent graft deployment should be tested in an attempt to promote complete thrombosis in the thoracic false lumen. False lumen embolization has been proved feasible for occlusion of post-TEVAR false lumen aneurysm.…”
Section: Discussionmentioning
confidence: 88%
“…The description of the MOTHER database study included 1010 cases, of which 114 cases were in the acute TBAD; the mean follow-up was 2.2 years; the conclusion reported that when performing TEVAR treatment for both thoracic aortic aneurysm and TBAD seems to offer remarkable mid-term protective effect from aortic-related mortality [26]. However, this protective effect seems to depend on the high rate of re-intervention of the aorta, which must be the focus of future training and equipment development.…”
Section: Discussionmentioning
confidence: 99%